Factorize 1 8 x 3 + 3 x 2 − 6 x .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Bwahahahaha nice solution
Log in to reply
Hehe yeah well if the multiple choice answer is stated this was I always check wat can't be the case... so this leaves only 1 answer here. Just stupid choices :)
1 8 x 3 + 3 x 2 − 6 x
= 3 x ( 6 x 2 + x − 2 )
= 3 x ( 6 x 2 + 4 x − 3 x − 2 )
= 3 x { 2 x ( 3 x + 2 ) − 1 ( 3 x + 2 ) }
= 3 x ( 3 x + 2 ) ( 2 x − 1 )
1 8 x 3 + 3 x 2 − 6 x = 3 x ( 6 x 2 + x − 2 ) = 3 x ( 6 x 2 + 4 x − 3 x − 2 ) = 3 x ( 2 x ( 3 x + 2 ) − 1 ( 3 x + 2 ) ) = 3 x ( 2 x − 1 ) ( 3 x + 2 )
1 8 x 3 + 3 x 2 − 6 x = 3 x ( 6 x 2 + x − 2 ) = 3 x ( 6 x 2 − 3 x + 4 x − 2 ) = 3 x ( ( 6 x 2 − 3 x ) + ( 4 x − 2 ) ) = 3 x ( 3 x ( 2 x − 1 ) + 2 ( 2 x − 1 ) ) = 3 x ( 2 x − 1 ) + 2 ( 2 x − 1 )
Problem Loading...
Note Loading...
Set Loading...
3 x ( 2 x − 1 ) ( 3 x + 2 ) is the only cubic polynomial